Evaluation of traditional and complementary medicine applications used in the covid-19 pandemic - KATRAN, HAMDİYE BANU (My University, 2023)
Objective: Traditional and complementary medicine practices have been used to protect and treat physical and mental diseases in different cultures and beliefs from past to present. In this study, it was aimed to determine which of the traditional and complementary medicine applications was used and its effectiveness in the pandemic. Methods: 979 people aged 18 and over (between 18 and 73) participated in the study. In the online survey, province, age, gender, occupation, education status, marital status, presence of children, presence of chronic diseases, COVID-19 diagnosis status, whether there is a COVID-19 vaccine, awareness of traditional and complementary medicine practices and nutritional and food supplements, utilization has been questioned. Results: It was observed that no nutritional and food supplements used by the participants before and during the coronavirus pandemic did not reduce the frequency of being diagnosed with COVID-19. Conclusions: In the study, it was observed that no food and nutritional supplement reduced the frequency of receiving COVID-19. However, in order to evaluate the effectiveness of nutritional and food supplements, it was concluded that the sample of the participants should be equal in terms of occupation, age, whether they were infected or no and that it should be supported by researches by questioning whether the patients diagnosed with COVID-19 had mild symptoms or not.
Keywords: Hemşirelik; Sağlık Bilimleri; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Supplement; pandemic; protect; traditional; complementary medicine